Optogenetic induction of chronic glucocorticoid exposure in early-life leads to blunted stress-response in larval zebrafish - Nagpal, Jatin; Eachus, Helen; Lityagina, Olga; Ryu, Soojin (European journal of neuroscience, 2024)
Early life stress (ELS) exposure alters stress susceptibility in later life and affects vulnerability to stress-related disorders, but how ELS changes the long-lasting responsiveness of the stress system is not well understood. Zebrafish provides an opportunity to study conserved mechanisms underlying the development and function of the stress response that is regulated largely by the neuroendocrine hypothalamus-pituitary-adrenal/interrenal (HPA/I) axis, with glucocorticoids (GC) as the final effector. In this study, we established a method to chronically elevate endogenous GC levels during early life in larval zebrafish. To this end, we employed an optogenetic actuator, beggiatoa photoactivated adenylyl cyclase, specifically expressed in the interrenal cells of zebrafish and demonstrate that its chronic activation leads to hypercortisolaemia and dampens the acute-stress evoked cortisol levels, across a variety of stressor modalities during early life. This blunting of stress-response was conserved in ontogeny at a later developmental stage. Furthermore, we observe a strong reduction of proopiomelanocortin (pomc)-expression in the pituitary as well as upregulation of fkbp5 gene expression. Going forward, we propose that this model can be leveraged to tease apart the mechanisms underlying developmental programming of the HPA/I axis by early-life GC exposure and its implications for vulnerability and resilience to stress in adulthood.
11. April 2024
Gesehen am 27.01.2025